Synchronous Necrotising Soft Tissue Infection: A Narrative Review of Presentation, Treatment and Outcomes - Xie, Yi; Seth, Ishith; Hunter-Smith, David J; Rozen, Warren M (Archives of Clinical and Medical Case Reports, 2024)
Background: Synchronous necrotising soft tissue infections (SNSTIs) are a rare and complex clinical phenomenon. Despite certain risk factors predisposing individuals to localized or single site NSTIs, the specific characteristics related to SNSTIs are not well-understood due to the lack of comprehensive epidemiological and clinical data. Methods: A thorough search of databases such as PubMed, Google Scholar, and Cochrane CENTRAL was performed up to April 2023. Interventional or observational studies focused on SNSTI were included. Information regarding epidemiology, causative agents, clinical signs, diagnostic methods, management, and patient outcomes were extracted and qualitatively synthesized. Results: SNSTIs present diagnostic challenges due to their varying and nonspecific symptoms, which contribute to increased morbidity and mortality rates. Our findings indicate that SNSTIs are typically caused by a single, gram-positive organism, differentiating them from localized NSTIs. There is a recognized need for the creation of new diagnostic tools, biomarkers, and treatments to enhance early identification and treatment of SNSTIs. Conclusion: SNSTIs present substantial diagnostic and treatment challenges, carrying higher mortality rates compared to localized NSTIs. More research is crucial to deepen our understanding of the pathophysiology, risk factors, and epidemiology linked to these infections. This will pave the way for improved management approaches and better patient outcomes.